2019
DOI: 10.1088/1612-202x/ab1bd9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal heating on the spectral composition and generation efficiency of terahertz radiation

Abstract: Heating of the electrons and lattice of the metal absorbing a femtosecond laser pulse causes a significant increase in the electron collision frequency. This leads to a substantial rise of the generated terahertz radiation field due to more efficient generation by drag force and the electron pressure gradient. Rapid changes in the electron temperature during the pulse are accompanied by the relative amplification of radiation at frequencies greater than the inverse incident pulse duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In most theoretical articles, the theory of THz wave emission under laser action on conducting media and plasma was constructed at a normal incidence of a focused laser pulse. Oblique incidence of a laser pulse on solid-state targets was considered in [13][14][15], when the effect of the generation of THz radiation can occur without focusing the laser radiation. In this paper, in contrast to [13][14][15] and for the first time, the emission of THz waves is analytically investigated for oblique incidence of laser radiation on rarefied plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most theoretical articles, the theory of THz wave emission under laser action on conducting media and plasma was constructed at a normal incidence of a focused laser pulse. Oblique incidence of a laser pulse on solid-state targets was considered in [13][14][15], when the effect of the generation of THz radiation can occur without focusing the laser radiation. In this paper, in contrast to [13][14][15] and for the first time, the emission of THz waves is analytically investigated for oblique incidence of laser radiation on rarefied plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Oblique incidence of a laser pulse on solid-state targets was considered in [13][14][15], when the effect of the generation of THz radiation can occur without focusing the laser radiation. In this paper, in contrast to [13][14][15] and for the first time, the emission of THz waves is analytically investigated for oblique incidence of laser radiation on rarefied plasma. It is shown that the energy of the THz wave packet has a maximum value at a grazing incidence of laser radiation, when its total reflection from the plasma boundary occurs.…”
Section: Introductionmentioning
confidence: 99%